Implementasi Bluetooth HC–05 untuk Memperbarui Informasi Pada Perangkat Running Text Berbasis Android - Akhmad Zainuri; Unggul Wibawa; Eka Maulana (Jurnal EECCIS, 2015)
Running Text Display is an information board in order to convey any information by  running text animation. This device is updated conventionally using a PC/notebook, so the updating process required by users  only in one place. User will be difficult to update the information, if they do not stay in the place or PC devices are not available. Alternative media to update and determine new information for dynamic running text device use the  data transfer capabilities between Android smart phone and microcontroller via HC-05 bluetooth module. The process of updating the data in the form of an array of characters successful transferred between Android applications and modules running text  are 90 % reliability with the furthest distance and through a barrier of 10.5 m and 9.4 m, respectively.